Higher education quality culture and Islamic work ethics effects on improving lecturer competence and performance - Herminingsih, Anik; Purnomo, Muhammad; Tristanti, Ika (International Journal of Innovative Research and Scientific Studies, 2025)
This research investigates the impact of higher education quality, culture and Islamic work ethics on improving lecturer competence and performance. In Indonesia, the competitiveness of higher education institutions remains moderate, and lecturers’ performance is crucial for achieving institutional goals. This study aimed to analyze how quality culture and Islamic work ethics influence lecturer competence and performance at Universitas Mercu Buana in Jakarta. A structured questionnaire was used to gather data from 145 lecturers, which was analyzed using Structural Equation Modeling (SEM) with AMOS software. The results indicate that while quality culture does not significantly affect lecturer competence, it has a positive and significant impact on lecturer performance. Additionally, Islamic work ethics significantly influence both lecturer competence and performance, with the strongest effect on performance through competence. These findings suggest that fostering a strong quality culture and promoting Islamic work ethics can significantly enhance the performance and competence of lecturers in higher education.